Mesenchymal stromal cells reprogram monocytes and macrophages with processing bodies. (9th November 2020) - Min, Hyunjung; Xu, Li; Parrott, Roberta; Overall, Christopher C.; Lillich, Melina; Rabjohns, Emily M.; Rampersad, Rishi R.; Tarrant, Teresa K.; Meadows, Norin; Fernandez-Castaneda, Anthony; Gaultier, Alban; Kurtzberg, Joanne; et al.
Abstract: Mesenchymal stromal cells (MSCs) are widely used in clinical trials because of their ability to modulate inflammation. The success of MSCs has been variable over 25 years, most likely due to an incomplete understanding of their mechanism. After MSCs are injected, they traffic to the lungs and other tissues where they are rapidly cleared. Despite being cleared, MSCs suppress the inflammatory response in the long term. Using human cord tissue-derived MSCs (hCT-MSCs), we demonstrated that hCT-MSCs directly interact and reprogram monocytes and macrophages. After engaging hCT-MSCs, monocytes and macrophages engulfed cytoplasmic components of live hCT-MSCs, then downregulated gene programs for antigen presentation and costimulation, and functionally suppressed the activation of helper T cells. We determined that low-density lipoprotein receptor-related proteins on monocytes and macrophages mediated the engulfment of hCT-MSCs. Since a large amount of cellular information can be packaged in cytoplasmic RNA processing bodies (p-bodies), we generated p-body deficient hCT-MSCs and confirmed that they failed to reprogram monocytes and macrophages in vitro and in vivo. hCT-MSCs suppressed an inflammatory response caused by a nasal lipopolysaccharide challenge. Although both control and p-body deficient hCT-MSCs were engulfed by infiltrating lung monocytes and macrophages, p-body deficient hCT-MSCs failed to suppress inflammation and downregulate MHC-II. Overall, we identified a novel mechanism by which hCT-MSCs indirectly suppressed a T-cell response by directly interacting and reprogramming monocytes and macrophages via p-bodies. The results of this study suggest a novel mechanism for how MSCs can reprogram the inflammatory response and have long-term effects to suppress inflammation. Abstract : Human umbilical cord tissue mesenchymal stromal cells (hCT-MSCs) suppress the activation of helper T cells by reprograming monocytes and macrophages. Monocytes and macrophages physically interact with hCT-MSCs via low-density lipoprotein receptor-related protein 1. After engagement, monocytes and macrophages engulf processing bodies within the cytoplasm of hCT-MSCs, then downregulate genes used to activate T cells.